Root Cause Analysis of Collapseable Aluminium Tube Failure on Lj-60 Type Impact Extrusion Press Machine Using The Fault Tree Analysis (FTA) Method - Jaya, Ezra Esa; Pratiwi, Swandya Eka (Universitas Mercu Buana, 2026)
The impact extrusion press machine is a machine that supports the manufacture of folded aluminium tubes. There are supporting components, namely dies and punch. These dies and punches have a lifespan and useful life. Checking and replacing needs to be done regularly because it has a big influence on the quality of the tube. This research aims to analyze product failure from impact extrusion press machines on the influence of parts on dies and punches. Folding aluminium tubes are often used for glue, ointment, cosmetics and others. During the production process, leaks and defects were found in the tube. Tube quality that does not meet standards will cause various problems. The influence of settings on dies, punches, skewed stamps results in the shape of the tube becoming ugly and unusable. The impact extrusion press machine and operator, apart from the dies and punch, also have a big influence on the results of collapsible aluminium tubes. Apart from these factors, continuous tilting pressure causes the mold to become chipped, scratched and damaged. The method used to analyze failure is the Fault Tree Analysis (FTA) method. Leak testing on collapsible aluminum tubes was also carried out. Total tube production for the 6 months from October 2023 – March 2024 is 29,758,430. The amount of production varies, January 2024 is the month with the highest production (5,180,872) and December 2023 is the month with the lowest production (4,791,760). From the results of data processing, the total defects in collapsible aluminum tubes for 6 months were 1,386,809. The number of defects varies, November 2024 is the month with the most defects (256,765) and December 2023 is the month with the lowest defects (196,901). The highest percentage of defects occurred in January 2024 (5.12%) and the lowest in December 2023 (4.11%).